PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA MENGGUNAKAN MODEL DISCOVERY LEARNING PADA MATERI GETARAN DAN GELOMBANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMP - Elfira S.H Hadis; Mursalin Mursalin; Dewi Diana Paramata (Universitas Negeri Gorontalo, 2022)
The purpose of this research is to produce science learning tools using the Discovery Learning model on vibration and wave material to improve student learning outcomes in junior high schools that are valid and suitable for theoretical use. The research method used is the development of a 4D model design which goes through 4 stages including the definition stage, the design stage, the development stage, and the dissemination stage. However, this research is only limited to the development stage. Data collection techniques are through expert validation sheets, practitioner validation sheets, and final semester students. According to the results of this research, it was obtained that implementation of learning by plan and teaching materials had a validity value of 0.85, while for student worksheets 0.87 and learning outcomes tests had a validity level of 0.84 with the criteria based on Aiken (V > 0.80). So that it can be concluded that theoretically it belongs to the very valid criteria and deserves to be tested by other researchers.